Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.devcel.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve-Derived CXCL12 and VEGF-A Regulate the Patterning of Arterial Vessel Branching in Developing Limb Skin

Abstract: SUMMARY In developing limb skin, peripheral nerves provide a spatial template that controls the branching pattern and differentiation of arteries. Our previous studies indicate that nerve-derived VEGF-A is required for arterial differentiation but not for nerve-vessel alignment. In this study, we demonstrate that nerve-vessel alignment depends on the activity of Cxcl12-Cxcr4 chemokine signaling. Genetic inactivation of Cxcl12-Cxcr4 signaling perturbs nerve-vessel alignment, and abolishes arteriogenesis. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(128 citation statements)
references
References 34 publications
5
118
1
1
Order By: Relevance
“…Among these, CXCR4 was increased by the presence of neurovascular interactions (Fig. 1G), and was induced by neurovascular interactions as with a CXCL12 receptor in a previous study (Li et al, 2013). Neuron-derived VEGFA reportedly stimulates arterial differentiation of ECs via neurovascular interaction (Mukouyama et al, 2005).…”
Section: Neurovascular Interactions In Developing Embryonic Mouse Limsupporting
confidence: 53%
See 1 more Smart Citation
“…Among these, CXCR4 was increased by the presence of neurovascular interactions (Fig. 1G), and was induced by neurovascular interactions as with a CXCL12 receptor in a previous study (Li et al, 2013). Neuron-derived VEGFA reportedly stimulates arterial differentiation of ECs via neurovascular interaction (Mukouyama et al, 2005).…”
Section: Neurovascular Interactions In Developing Embryonic Mouse Limsupporting
confidence: 53%
“…Specifically, peripheral neuron-derived Cxcl12 stimulates EC migration as an attractive cue for the recruitment and alignment of distant vessels with nerves (Li et al, 2013). Hence, several of the neuron-derived factors that are involved in neurovascular interactions have been described, although the ensuing EC-mediated intracellular signaling pathways that lead to neurovascular parallelism have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The lumina of the present constructs are much wider, and thus invasion by vessel precursors should be easier. Moreover, it has been found that Schwann cells secrete VEGF and are instrumental in differentiating endothelial cell precursors to blood vessels: the geometrical lay-out of nerves becomes a template for patterning the development of the arterial network [89][90][91]. It is thus expected that, once implanted, our constructs would be easily vascularized, ensuring early as well as long-term viability of the biohybrid.…”
Section: Discussionmentioning
confidence: 97%
“…Our approach to examining the effects of AMD3100 in a complex in vitro microenvironmental model of neovascularization may prove significant for understanding the mechanisms of action of this and other drugs and associated molecules in promoting or inhibiting revascularization and for more clearly defining the experimental approach to testing or assessing the effects of such drugs in vitro and subsequently in vivo. Understanding such mechanisms as those exemplified here with CXCL12 in new blood vessel formation has translational implications that include inhibition of tumor progression and promotion of tissue repair and regeneration as diverse as peripheral arterial disease and ischemic injury, burn injury, neurodegenerative disease, and hematological regeneration [5][6][7]11,18,22,[56][57][58][59][60].…”
Section: Fig 6 Cd31 Blocks Integration Of Exogenous Huvecs Into Immmentioning
confidence: 99%
“…These include hematopoietic stem/ progenitor cell (HSC/HPC) trafficking, immune surveillance, blood vessel, cardiac and central nervous system formation during development, revascularization at sites of tissue injury, and the initiation and metastatic spread of tumors [1][2][3][4][5][6][7][8][9]. CXCL12 plasma levels are rapidly elevated in response to tissue damage, with increased CXCL12 concentrations correlating with the severity of injury, increased vascular endothelial growth factor (VEGF) plasma levels, and the associated rapid mobilization of proangiogenic cells into the circulation [10,11].…”
Section: Introductionmentioning
confidence: 99%